2016
DOI: 10.1055/s-0035-1565184
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nalmefene and Naltrexone in Alcohol Dependence: Are there any Differences? Results from an Indirect Meta-Analysis

Abstract: This indirect meta-analysis indicates an advantage of nalmefene over naltrexone. Nalmefene is an effective and well-tolerated medication for the reduction of alcohol consumption. Additional data are necessary to demonstrate possible advantages of nalmefene over naltrexone in the treatment of alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…In disagreement with the above statement, reported to NICE, a Lundbeck‐sponsored indirect comparison of nalmefene and naltrexone was published recently and found a superiority of nalmefene . Inclusion criteria in this meta‐analysis were close to ours, except that we were more stringent concerning the duration of the abstinence period allowed before entering the trial.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In disagreement with the above statement, reported to NICE, a Lundbeck‐sponsored indirect comparison of nalmefene and naltrexone was published recently and found a superiority of nalmefene . Inclusion criteria in this meta‐analysis were close to ours, except that we were more stringent concerning the duration of the abstinence period allowed before entering the trial.…”
Section: Discussionmentioning
confidence: 78%
“…All disagreements were resolved by consensus or by consultation with another reviewer (F.N.). To avoid omission of any studies, all the references identified were compared to (1) references included in a previous comprehensive meta‐analysis on pharmacotherapy of alcohol use disorders that were shared by the author and (2) references included in a previous indirect comparison of nalmefene and naltrexone .…”
Section: Methodsmentioning
confidence: 99%
“…NF is a new pharmacological treatment used to reduce alcohol consumption, which offers some clinical advantages compared to NX and NT (Soyka et al., ). The scientific bases of its effectiveness in reducing alcohol abuse are that this compound is an antagonist of the μ ‐opioid receptor, but is also a partial κ‐opioid receptors agonist (Nealey et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Naltrexone and nalmefene are pharmacotherapies approved for the treatment of alcohol use disorders (AUD), in different countries (Castera et al, ; Mann, Bladstrom, Torup, Gual, & van den Brink, ; Soyka, Friede, & Schnitker, ). Naltrexone is also approved for the treatment of opioid use disorders, most recently as an intramuscular depot formulation (Lee et al, ; Woody & Metzger, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, comparative data on the effects of naltrexone and nalmefene in humans are extremely limited (Soyka et al, 2016). To our knowledge, there has been only one study that directly compared an effect of nalmefene and naltrexone in humans (Drobes, Anton, Thomas, & Voronin, 2004;Soyka et al, 2016). This is the first study to compare neuroendocrine effects of naltrexone and nalmefene in humans, using an intravenous (IV) route of administration.…”
mentioning
confidence: 99%